Pemanfaatan Literasi Digital dalam Pembelajaran Sejarah Kelas XI IPS SMAS Mujahidin Pontianak - Putri, Rina Raihana; Chalimi, Ika Rahmatika; Mirzachaerulsyah, Edwin (Peneliti.net, 2025)
In today's digital era, of course, it provides opportunities and benefits. Especially in the world of education, the presence of digital literacy in the field of education and teaching is a form of collaboration with existing progress. This update certainly brings new experiences in the world of education. This research is qualitative with descriptive method. The subjects in this study are history teachers, students and curriculum waka. The data acquisition process is carried out through observation, documentation and interviews. In this study, the data interpetation method was carried out by reduction, presentation, and finally drawing conclusions. The results of the study show that : 1) Teacher strategies in utilizing digital literacy in history learning in detail have been listed in the RPP. 2) In implementation process, digital literacy is used in material delivery & evaluation. Material delivery utilizes tools in the form of media, as well as digital sources. In the evaluation process, assignments are given in groups. The digital literacy used is access to digital sources form journals, youtube and other digital sources. 3) Obstacles in its implementation, namely first, technical obstacles in the form of internet network capabilities and lack of supporting infrastructure. Second, non-technical obstacles include a less conducive environment and a lack of student digital literacy skills. Thrid, internal constraints from teacher. It can be concluded that the use of digital literacy is an effort to adapt the learning process and current development.